2013
DOI: 10.1002/col.21821
|View full text |Cite
|
Sign up to set email alerts
|

Color change of white spot lesions after resin infiltration

Abstract: This study evaluates color change of the enamel lesion before and after resin infiltration and after thermocycling (TC) in order to assess clinical usefulness of resin infiltrant in restoring esthetics of incipient enamel caries lesions. Twenty‐five healthy premolars were prepared and crown portions were vertically cut. Specimens were emerged in acryl blocks with relatively flat proximal surface facing outside. Specimens were put in decalcification solution (50 mM acetic acid solution, 3 mM CaCl2·H2O, 3 mM KH2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
5
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
3
5
0
3
Order By: Relevance
“…It may also be attributed to the fact that Coca‐Cola is darker than Redbull beverage . Ourcolor results came in agreement with those of Bak et al and Yetkiner et al who proved the ability of resin infiltrant to resist thermal and discoloration challenges. Regarding surface roughness, our results agreed with previous studies which concluded that resin infiltration of enamel lesions can provide and maintain smoother surface.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It may also be attributed to the fact that Coca‐Cola is darker than Redbull beverage . Ourcolor results came in agreement with those of Bak et al and Yetkiner et al who proved the ability of resin infiltrant to resist thermal and discoloration challenges. Regarding surface roughness, our results agreed with previous studies which concluded that resin infiltration of enamel lesions can provide and maintain smoother surface.…”
Section: Discussionsupporting
confidence: 92%
“…Resin infiltration has become a promising treatment option for incipient white lesions (WSLs) of enamel . However, concerns still exist regarding its ability to resist degradation by different factors in the oral cavity …”
Section: Discussionmentioning
confidence: 99%
“…Based on this idea, a greater color change (Δ E *) was observed in the group treated with a resin infiltrant after bleaching than for the other groups. The color alteration of WSLs are similar to previous studies which showed an increased Δ E * values in both bleaching and resin infiltration groups.…”
Section: Discussionsupporting
confidence: 89%
“…(b) SEM view of the cross-sections of the bleached/resininfiltrated lesions revealed a distinct ultramorphologies like as holes and column gaps were observed amongst the cured resin material (red arrows) (at viewed at 5,000 times magnification) FIG URE 3 (a) SEM view of the eroded area in the demineralized enamel after etching for 120 s with HCl acid gel showing the dissolution of the enamel surface layer and the expose of the underlying layer (red arrows) (as viewed at 1,000 times magnification). (b) SEM view showing the penetration of the resin infiltrant into the spaces formed in the HCL acid-applied demineralized enamel seen in Fig.3a (red arrows) (as viewed at 1,000 times magnification) HORUZTEPE AND BASEREN | 383alteration of WSLs are similar to previous studies9,32,33 which showed an increased DE* values in both bleaching and resin infiltration groups.…”
supporting
confidence: 81%
“…The intraoral colourimeter used in this study was reported to represent CIE values with high accuracy and reproducibility. It also has a suitable tip size to measure the value on the labial surface of the primary incisor; however, the CIE Lab results from the present study may not be considered as the absolute reference values because there may be variability depending on the different type of measuring devices. Nevertheless, the results presented in this study may be helpful to understand the characteristics of the colour change of primary incisors after trauma.…”
Section: Discussionmentioning
confidence: 94%